Biology Learning Based on Brain-Based Learning Using Cocoon Finger Puppet - Jekti Prihatin; Sri Suwartini; Sylvia Anggraeni; Karimatul Aini; Ridlo Firmansyah (BIOEDUKASI, 2017)
Biology learning by playing, especially using cocoon finger puppet role-playing, is fundamental for students. The article is aimed to know how brain-based learning role-playing by using finger puppet cocoon can increase the student’s enthusiasm and learning outcomes in biology. The research occupied two-cycle lesson study. The datawere collected by using observation sheet and video recording of the learning activities in the classroom. The result showed that brain-based learning role-playing by using cocoon finger puppet enhanced the students' enthusiasm, excitement and learning outcomes. Key words: brain-based learning, cocoon, finger puppet, role-playing.